Understanding Nepali Nationalism. (December 2016) - Bhandari, Kalyan
Abstract: This article explores the foundations of Nepali nationalism and its articulation in contemporary Nepal. It makes informed readings of the historical antecedents of Nepali national identity and argues that Nepali national identity was forged in an attempt to create and maintain a boundary with 'outsiders' – mainly India and China. Data collected through online content analysis of the editorial commentary pages of two Nepali print media, followed by in‐depth interviews, show that in the changed political context, the boundary still persists though its narrative has changed. This article argues that the expression of Nepali nationalism can be understood as the maintenance of this boundary; its forms and articulation shaped by the changing political contexts.